Matching salt intake to physiological need in rats using foraging protocols - Rowland,N.E. (2007)
Several studies of the quantitative relationship between sodium need and sodium intake in rats are reviewed. Using acute diuretic treatment 24 h beforehand, intake matches need fairly accurately when intake is spread out in time by using a hypotonic solution of NaCl. In contrast, using a hypertonic solution, intake is typically double the need. Using the same diuretic treatment, although the natriuresis occurs within ~1 h, the appetite appears only slowly over 24 h. Increased plasma levels of aldosterone parallel the increased intake; however, treatment with metyrapone blocks the rise in aldosterone but has no effect on appetite. Satiation of sodium appetite was studied in rats using sodium loss induced by chronic diuretic treatment and daily salt consumption sessions. When a simulated foraging cost was imposed on NaCl access in the form of a progressive ratio lever press task, rats showed satiation for NaCl (break point) after consuming an amount close to their estimated deficit. The chronic diuretic regimen produced hypovolemia and large increases in plasma aldosterone concentration and renin activity. These parameters were reversed to or toward non-depleted control values at the time of behavioral satiation in the progressive ratio protocol. Satiation mechanisms for sodium appetite thus do appear to exist. However, they do not operate quantitatively when concentrated salt is available at no effort, but instead allow overconsumption. There are reasons to believe that such a bias toward overconsumption may have been beneficial over evolutionary time, but such biasing for salt and other commodities is maladaptive in a resource-rich environment.